Laparoscopic versus open liver resection for hepatocellular carcinoma in elderly patients: A systematic review and meta-analysis of propensity score-matched studies - Wang, Shi; Ye, Guanxiong; Wang, Jun; Xu, Shengqian; Ye, Qiaoping; Ye, Hailin (Frontiers in Oncology, 2022)
Purpose Laparoscopic liver resection (LLR) is a widely practiced therapeutic method and holds several advantages over open liver resection (OLR) including less postoperative pain, lower morbidity, and faster recovery. However, the effect of LLR for the treatment of hepatocellular carcinoma (HCC) in elderly patients remains controversial. Therefore, we aimed to perform the first meta-analysis of propensity score-matched (PSM) studies to compare the short- and long-term outcomes of LLR versus OLR for elderly patients with HCC. Methods Databases including PubMed, Embase, Scopus, and Cochrane Library were systematically searched until April 2022 for eligible studies that compared LLR and OLR for the treatment of HCC in elderly patients. Short-term outcomes include postoperative complications, blood loss, surgical time, and length of hospital stay. Long-term outcomes include overall survival (OS) rate and disease-free survival (DFS) rate at 1, 3, and 5 years. Results A total of 12 trials involving 1,861 patients (907 in the LLR group, 954 in the OLR group) were included. Compared with OLR, LLR was associated with lower postoperative complications (OR 0.49, 95% CI 0.39 to 0.62, P < 0.00001, I2 = 0%), less blood loss (MD −285.69, 95% CI −481.72 to −89.65, P = 0.004, I2 = 96%), and shorter hospital stay (MD −7.88, 95% CI −11.38 to −4.37, P < 0.0001, I2 = 96%), whereas operation time (MD 17.33, 95% CI −6.17 to 40.83, P = 0.15, I2 = 92%) was insignificantly different. Furthermore, there were no significant differences for the OS and DFS rates at 1, 3, and 5 years. Conclusions For elderly patients with HCC, LLR offers better short-term outcomes including a lower incidence of postoperative complications and shorter hospital stays, with comparable long-term outcomes when compared with the open approach. Our results support the implementation of LLR for the treatment of HCC in elderly patients. Systematic review registration https://inplasy.com/inplasy-2022-4-0156/, identifier INPLASY202240156.